PREVALENCE OF DEPRESSION AND RELATED FACTORS AMONG OLDER PATIENTS WITH VESTIBULAR DISORDERS (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of depressive disorder and analyze associated factors among older adults with vestibular dysfunction who were hospitalized at Bach Mai Hospital.Methods: A cross-sectional descriptive study was conducted on 84 patients aged 60 years and older diagnosed with vestibular dysfunction from August 2024 to March 2025. Depression was screened and assessed using the Hamilton Depression Rating Scale. Data were analyzed using SPSS version 25.0.Results: The prevalence of depressive disorder among the patients was 29.8%, with severe depression accounting for the highest proportion (15.5%). Analysis of associated factors showed that several clinical characteristics were significantly associated with an increased risk of depression (p < 0.05), including a history of vestibular disorders (p = 0.009), the presence of tinnitus (p < 0.001), prolonged duration of dizziness symptoms (p < 0.001), and a frequency of three or more dizziness episodes per week (p < 0.001).Conclusions: Depressive disorder represents a significant health burden among older patients with vestibular dysfunction and is closely associated with the severity of physical symptoms. Routine psychological assessment should be considered in the management of patients with vestibular disorders.
Keywords: Vestibular dysfunction, depression, HAM-D.